Invasive Foreign Vegetation Analysis on Forest Revitalization Area Block Argowulan National Park Bromo Tengger Semeru National Park - Zulharman Zulharman (Natural B, Journal of Health and Environmental Sciences, 2017)
The aim of the research was to identify the invasive alien plant species and the pattern of the spread and diversity of invasive alien plants in the area of revitalization forest Block Argowulan Bromo Tengger Semeru National Park. This research was conducted in the area of revitalization forest Block Argowulan, Mount Penanjakan Bromo Tengger Semeru National Park (TNBTS) Malang, was from June 2014 through February 2015 by using sampling vegetation analysis method. The invasive alien plant species were found such as Ageratina riparia, Acacia decurrens, Tithonia diversifolia and Imperata cylindrica with the pattern of spread of clumped (clumped) and the Diversity variety, the type that was able to change the ecosystem, namely Acacia decurrens and Imperata cylindrica, because contained residues which capable of causing other plants can not grow. The strongest association of Acacia decurrens was with Ageratina riparia, indicated by Ochiai index of 0.03; Dice index of 0.23; Jaccard index and 0.30 index value close to 1.